Fault Tolerant Systems : Building Reliability through Observability, Incident Response, and Problem Management - Ageev, Aydar (2025)
This Master’s Thesis introduces the Fault Tolerance Production System Framework (FT-PSF), a practical model for constructing fault-tolerant systems as an iterative operational process. The framework defines a closed reliability loop—spanning Critical User Journeys (CUJs), Service Level Indicators (SLIs), Service Level Objectives (SLOs), and Error Budgets—to quantify and act on real user impact. It integrates observability, incident response, and structured postmortem analysis into a unified reliability workflow. Applied as an explanatory framework to SAP Concur’s production environment, FT-PSF offers a systems-level understanding of how fault tolerance emerges through layered observability, continuous feedback, and operational discipline.